Beyond The Standard: Achieving Functional and Aesthetic Excellence in Unilateral Macrostomia Repair with Buccal Flap and Multi Z-Plasty Technique in Infancy - Bimayudo Aprialdi; Affandi Wiramur; Rafeni Bunga Cikita (Jurnal Plastik Rekonstruksi, 2026)
Introduction: Macrostomia is a rare congenital craniofacial anomaly that significantly affects feeding, speech, aesthetics, and psychosocial well-being. Early surgical intervention using advanced techniques is essential to restore anatomical integrity and improve functional outcomes. This case report presents the management of a five-month-old female infant with a unilateral left-sided macrostomia (Tessier Cleft-7) using a combination of buccal flap and multiple Z-plasty techniques.Case Presentation: The patient presented with a unilateral left-sided macrostomia since birth, accompanied by feeding difficulties characterized by choking and audible “blup-blup” sounds during feeding. Physical examination confirmed a moderate unilateral macrostomia without signs of infection or systemic illness. Preoperative assessments, including laboratory tests and multidisciplinary consultations, confirmed the patient’s fitness for surgery.Discussion: Surgical repair was performed with a multi-layer closure approach, utilizing a buccal flap for the inner layer and multiple Z-plasty for the outer layer to achieve tension-free closure and optimal aesthetic results. This technique aligns with contemporary trends favoring individualized, anatomy-driven repairs over traditional methods. The absence of intraoperative and postoperative complications and the satisfactory functional and cosmetic outcomes underscore the effectiveness of this approach. Compared to conventional linear closure techniques, multiple Z-plasty minimize scar contracture and enhance commissural symmetry, particularly in complex cases of macrostomia. This case highlights the critical role of multidisciplinary collaboration and tailored surgical planning in addressing the anatomical challenges of macrostomia and achieving optimal reconstructive outcomes.Conclusion: Early, multidisciplinary management of macrostomia using combined buccal flap and multiple Z-plasty techniques can achieve excellent functional and aesthetic outcomes with minimal complications. This case contributes to the growing literature supporting anatomy-specific surgical approaches and comprehensive perioperative care in macrostomia reconstruction.